2016
DOI: 10.2147/ijn.s97177
|View full text |Cite
|
Sign up to set email alerts
|

A novel dissolution media for testing drug release from a nanostructured polysaccharide-based colon specific drug delivery system: an approach to alternative colon media

Abstract: The aim of this study was to develop a novel microbially triggered and animal-sparing dissolution method for testing of nanorough polysaccharide-based micron granules for colonic drug delivery. In this method, probiotic cultures of bacteria present in the colonic region were prepared and added to the dissolution media and compared with the performance of conventional dissolution methodologies (such as media with rat cecal and human fecal media). In this study, the predominant species (such as Bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In the past 5 years, efforts have been made to develop a medium containing probiotic that can provide an effective alternative to rat cecal content. [ 13 14 15 ] The present work has established that the use probiotic containing medium may be extended to various dosage forms prepared using different polysaccharides and is not limited by the nature of formulation or types of polysaccharides used.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the past 5 years, efforts have been made to develop a medium containing probiotic that can provide an effective alternative to rat cecal content. [ 13 14 15 ] The present work has established that the use probiotic containing medium may be extended to various dosage forms prepared using different polysaccharides and is not limited by the nature of formulation or types of polysaccharides used.…”
Section: Resultsmentioning
confidence: 94%
“…[ 1 ] This challenge is further intensified by the diverse strategies used in the formulation of colon-targeted delivery systems, their release being designed to be facilitated by stimuli such as pH,[ 2 3 ] pH and time,[ 2 ] presence of enzymes,[ 4 ] time,[ 6 7 8 9 ] using prodrug based,[ 7 ] pressure controlled,[ 10 ] and microbially triggered delivery systems. [ 11 12 13 14 15 16 17 18 ] The most commonly reported medium to evaluate all these types of delivery systems is the one that utilizes colon contents of rodents. [ 5 ] However, this medium has some serious limitations including lack of reproducibility, high cost, complexity of procedure, and vivisection.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the probiotic release media is presented in Table 4. In a similar study by Kotla et al [146], a probiotic culture was once again used to mimic the colonic environment to examine drug release from 5-fluorouracil granules coated with polysaccharides. The species used are listed in Table 4.…”
Section: In Vitro Release Methodsmentioning
confidence: 99%
“…In this study, the drug release profiles obtained from the tests with probiotic mixture, rat caecum content and human fecal slurries were to some extent comparable. In general, the probiotic mixture resulted in a slightly faster release than the other two media [146]. Unfortunately, the choice of bacteria was not thoroughly discussed in these articles although the authors suggested that these bacteria can simulate the conditions in the colon.…”
Section: In Vitro Release Methodsmentioning
confidence: 99%
“…The bag remains suspended in 10 mL of dissolution media (phosphate buffer pH 6.8 by 0.5% v/v tween 80) in a beaker, employed in a rotary shaker at 37°C and rotated at 100 rpm. Aliquots of EE ( % ) = (Amount of drug in (mg) ∕ Amount of drug added (mg)) × 100 8 mL sample remain introverted at particular time intervals and substituted through fresh 8 mL of dissolution media to sustain the sink conditions (Kotla et al, 2016). The quantity of drugs released at numerous time points remains estimated through UV-Visible spectroscopy procedure.…”
Section: Entrapment Efficiency (Ee)mentioning
confidence: 99%